STRATEGY OF RAISING ALUMNI DONATIONS: AN ALTERNATIVE FOR FINANCING A HIGHER EDUCATION - Zahruddin, Zahruddin; Asyari, Hasyim; Munadi, Muhammad (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to describe the strategy of raising alumni donation in a higher education. A higher education for the developed countries has a big and important role, not only in producing competent graduates in their fields but also as the driving force for the development of economy and civilization. The government has an interest and encourages a higher education to play more role. Therefore, the government issues a policy related to the autonomy of higher education which is known university with status of legal entity. University of Indonesia is one of the universities that has the status. Consequence of the status is subsidy cuts. To overcome the problem, University of Indonesia looks for one of new sources which is alumni donation. The method used in this research is descriptive-qualitative. Collecting data uses the techniques of observation, interview, and documentation study. The result of research indicates that decisions taken by University of Indonesia as legal entity state university are strategic innovative, and attractive including the change of structure, innovation of programs, classification of alumni, and non-money donation.